Grey Oxisol from the Jequitinhonha Valley, Minas Gerais, Brazil: a conceptual challenge to the soil classification system? - Silva, A. C.; Murad, E.; Fabris, J. D.; De Souza, S.; Fabris, S. D. S.; Mendes Pires, M. J .; Pires, M. J. Mendes; Pereira, M. C.; Guimarães, A. O.; Vargas, H.; Ardisson, J . D D. (Clay Minerals, 2015)
AbstractThe upper Jequitinhonha Valley is located within the Serra do Espinhaço Meridional mountain range in the State of Minas Gerais, Brazil. The topography is flat or gently undulating with large flat areas known aschapadas(‘high plains’) that are dissected by rivers forming swamps known locally asveredas(‘paths’). The present study is concerned mainly with a representative toposequence in the watershed of the Lagoa do Leandrovereda, a swamp near the city of Minas Novas on a chapada of the highlands of the Alto (Upper) Jequitinhonha region.The soils of this sequence were studied by a variety of physical and chemical techniques, including Mössbauer, electron spin resonance (ESR) and photoacoustic (PAS) spectroscopies, as well as X-ray diffraction (XRD) and carbon isotope data. Mössbauer spectra of the silt fraction of a grey Xanthic Haplustox (Munsell 10YR 3/2) from the Lagoa do Leandrovereda, referred to here as a ‘Grey Haplustox’ (‘LAC’), proved the existence of Fe2+- and Fe3+-bearing components. Photoacoustic spectroscopy confirmed the presence of Fe2+, as shown by Mössbauer spectroscopy, probably in an octahedrally coordinated site, but the principal optical absorption bands are due to different Fe3+sites. A ferrimagnetic contribution and three other paramagnetic lines attributed to Fe3+and Ti3+were demonstrated by means of ESR. The ESR and PAS results are thus in agreement with the chemical composition and Mössbauer spectroscopy, allowing a detailed characterization of the mineralogy of this silt.Carbon isotope data indicate the climate to have varied during the past: awetter climate in the Pleistocene, with drier phases in the Late Pleistocene and Holocene, and again a more humid climate 1200 years ago. δ13Cdata indicate the C3scrubland vegetation to have occupied the bottom of theveredain the past (Bispo & Silva, 2014).Greyish Oxisols that consist chiefly of phyllosilicate minerals of the kaolinite group (which are usually associated with binary oxides and hydroxides) are of common occurrence in tropical soils resulting from leaching and precipitation. Such Oxisols of greyish appearance and similar mineralogy have been described elsewhere from Brazil and, for example, from India. Such soils are therefore proposed here as a new hierarchical level of the Soil Classification System.